FractalNet-based key generation for authentication in Voice over IP using Blockchain - Vajjala Sreenivasulu; Chinthaginjala Ravikumar (Ain Shams Engineering Journal)
Voice over Internet Protocol (VoIP) has seen significant growth since the proliferation of the Internet, primarily due to its low-cost structure and simplicity in deployment. However, VoIP systems face critical security challenges, including threats to integrity, authenticity, and confidentiality. Addressing these concerns necessitates the development of a secure and efficient key agreement and authentication framework. Thus, this paper proposes a new deep learning technique called FractalNet-based key generation (FractalNet-keyGen) for authentication in VoIP using Blockchain. The implementation of the proposed methodology is as follows: Here, several entities, such as VoIP users, admin, smart contract, as well as minor nodes are considered. Moreover, the steps that are considered include Blockchain association, Registration, Initialization, Authentication, Key generation, as well as Verification. Besides, the established FractalNet-keyGen approach attained improved performance with values of validation time, memory usage, response time, key complexity, packet loss ratio, latency, and jitter of 20.37 sec, 15.35 MB, 2.06 sec, 0.942, 1.85%, 0.302s, and 0.275s.